Pengaruh Iklim Organisasi Dan Komitmen Organisasi Terhadap Organizational Citizenship Behaviour Di Kantor SAMSAT Kota Metro - Yateno; Deny Edy Widodo; Didik Santoso (Jurnal Manajemen DIVERSIFIKASI, 2024)
The purpose of this research is to test whether organizational climate and organizationalcommitment either partially or simultaneously have a role in influencing organizationalcitizenship behavior at the Metro City Samsat Office. The design of this study usesquantitative, the number of samples found in employees is 32 respondents. The samplingtechnique uses census sampling. Data analysis used validity and reliability tests, prerequisitetests used normality, linearity and homogeneity. And analysis of decision making usingmultiple regression with partial test (t), simultaneous (f) and the coefficient of determination.The results of the analysis prove that organizational climate and organizational commitmentboth partially and simultaneously have a role in influencing organizational citizenshipbehavior, meaning the behavior of employees who voluntarily do work beyond the standardassignment given to them, in order to help the company's sustainability. achieve its goals soas to incr